2015
DOI: 10.1002/sea2.12038
|View full text |Cite
|
Sign up to set email alerts
|

Postdisaster reciprocity and the development of inequality in personal networks

Abstract: Within the context of major changes in economics, population distribution, and lifestyles around the world, people continue to rely on personal relationships for support. People also often create or find themselves in relationships that are alternatively asymmetrical or balanced. In this study, we are interested in how people face acute or chronic hazards and how asymmetrical or balanced exchange relationships are associated with different types of social support in these contexts. This study examines the degr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Examining the risk population's demographic characteristics (gender, age) is vital for any research. Numerous studies have been conducted on the influence of demographic factors on risk perception (Armaş & Avram, 2008;Jones et al, 2013;Rahman, 2019;. The most common results obtained in research on demographic determinants of risk perception are that women perceive risks more than men, while patterns are not observed in other aspects of demographic factors (Sund et al, 2017).…”
Section: Literary Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Examining the risk population's demographic characteristics (gender, age) is vital for any research. Numerous studies have been conducted on the influence of demographic factors on risk perception (Armaş & Avram, 2008;Jones et al, 2013;Rahman, 2019;. The most common results obtained in research on demographic determinants of risk perception are that women perceive risks more than men, while patterns are not observed in other aspects of demographic factors (Sund et al, 2017).…”
Section: Literary Reviewmentioning
confidence: 99%
“…However, it is necessary to work on improving knowledge and preparedness in all age categories. Research conducted in Mexico and Ecuador aimed to determine how residents of cities where natural disasters have occurred perceive risk and their estimates for future events (Jones et al, 2013). The results showed that younger people think that it is very likely to experience a disaster again.…”
Section: Literary Reviewmentioning
confidence: 99%
“…Th ese lines of inquiry have also been important to ethnographic work around ethics of care, and strategies such as "intravention" (Bailey 2009; Cheng and Garriga-López 2021) that communities can provide for one another when services and resources are scare or outright denied (Duclos and Sánchez Criado 2019;Nelson 2016). Th e increased attention to networks of mutual aid in the context of disasters (Jones et al 2015;Rodríguez Soto 2020) speaks to these concerns through a diff erent lens.…”
Section: Medical and Environmental Anthropologiesmentioning
confidence: 99%
“…; Jones et al. ); and individually and internally differentiated human agencies (Barrios ; Fortun ; Hilhorst ).…”
Section: Introductionmentioning
confidence: 99%